Удосконалення моделей та методів радіоакустичного і акустичного зондування атмосферного граничного шару - Лю, Чан (My University, 2012)
У дисертаційній роботі автором сформульовано ряд нових задач методу акустичного зондування (АЗ) і обґрунтовано їх необхідність. Для адекватної оцінки загального рівня розсіяння звукових хвиль при A3 атмосферного граничного шару (АГШ) доказано необхідність урахування стискання середовища. Проведено аналіз руху зондуючого пакета акустичних хвиль у ламінарному потоці при стійкій стратифікації АГШ, на основі якого розроблено основи методики вимірювань швидкості ламінарних потоків і обґрунтовано необхідність включення фазометрів у схеми приймальних пристроїв содарів. Обґрунтовано можливість використання наближення Френеля, завдяки чому отримано аналітичні вирази для прийнятого сигналу з нижньої частини траси зондування. Ці вирази дозволяють отримати розрахункові дані, на підставі яких можна проводити корекцію результатів вимірювань і виключити методичну похибку вимірювання метеопараметрів у нижній частині траси зондування. Solution of a scientific and applied problem, making it possible to increase information methods for remote sounding of atmospheric boundary layer based on the use of acoustic waves, is presented in the given thesis. A number of new acoustic sounding method problems are formulated on the basis of the physical factors through analysis and their necessity is substantiated. In particular, the need for the medium compression inclusion is substantiated for the adequate estimation of the general level of the sounding waves scattering at AS atmospheric boundary layer. The analysis of the acoustic waves sounding packet motion in the laminar flow at the atmospheric boundary layer stable stratification was carried out, the foundations of the methods for the laminar flows were developed on this analysis basis and the necessity for including the phase meters into the circuit of the receiving sodar devices was substantiated. At the analysis of the diffraction problem of the electromagnetic waves scattering on the air permittivity inhomogeneities being formed when acoustic waves pass in the low part of the route of the radio acoustic sounding bistatic systems, the possibility to use Fresnel approximation is substantiated, due to this the analytical expressions for the received signal in the bistatic approximation are derived. These expressions make it possible to receive the calculation data, using them it is possible to carry out correction of the measurement results and exclude the systematic error of meteorological parameters measurement at the low part of the sounding route.
Keywords: атмосферний граничний шар; содар; радіоакустичне зондування; дифракційні задачі; atmospheric boundary layer; sodar; radio acoustic sounding; diffraction tasks